Dyke demolition led to a sharp decline in waterbird diversity due to habitat quality reduction: A case study of Dongting Lake, China. Issue 4 (31st March 2022) - Zhu, Feng; Zou, Yeai; Zhang, Pingyang; Zhang, Siqi; Chen, Xinsheng; Li, Feng; Deng, Zhengmiao; Zhang, Hong; Yu, Zhibing; Zhu, Xiaoyong; Xie, Yonghong; Zou, Dongsheng
Abstract: Dongting Lake, an important wintering habitat for migratory waterbirds in the East Asian–Australasian Flyway, has suffered serious degradation in recent decades. To restore habitats for biodiversity conservation and flood control, 459 dykes were demolished and 14 were preserved in 2017. However, the direct impact of dyke demolition on wintering waterbirds was not comprehensively assessed. In this study, based on annual waterbird census and habitat data (2013/14–2020/21), we compared the differences in habitat areas and species composition of waterbirds in the dyke‐demolished and preserved areas, and explored whether habitat changes caused by the dyke demolition were responsible for the changes in the number of species and percentages of waterbird individuals. The results indicate that the areas of water (including shallow water) and mudflat habitats significantly decreased, but the vegetation area significantly increased in the dyke‐demolished areas. The species numbers and percentages of waterbird individuals at the community and foraging guilds levels, and the percentages of nine species, were higher in the dyke‐preserved areas than those in the dyke‐demolished areas. Changes in the numbers of species and percentages of individuals of fish eaters, insectivores, and omnivores positively correlated with drastic changes in the percentages of water habitats (including shallow water) after dyke demolition. Effective measures should be carried out to restore hydrological regimes, providing waterbirds sufficient suitable habitats with different water depths. These findings improve our understanding of the influence of dyke demolition on waterbirds and provide insights for wetland management and waterbird conservation. Abstract : Dyke demolition led to a sharp decline in waterbird diversity at the community, foraging guilds, and species levels. Habitat changes caused by dyke demolition were responsible for the changes in waterbird diversity.